Agricultural sector credit and output relationship in Nigeria: Evidence from nonlinear ARDL1 - Olorunsola E. Olowofeso; Adeyemi A. Adeboye; Valli T. Adejo; Kufre J. Bassey; Ochoche Abraham (CBN Journal of Applied Statistics, 2017)
This paper investigates the relationship between credit to agriculture and agricultural output in Nigeria by means of nonlinear autoregressive distributed lag (NARDL) model using a time series data from 1992Q1 to 2015Q4. Results show no evidence of asymmetry in the impact of credit to output growth in the agricultural sector (positive and negative changes) in the short-run, but different equilibrium relationships exist in the long-run. The dynamic adjustments show that the cumulative agricultural output growth is mostly attracted by the impact of the positive changes in credit to agriculture with a lag of four quarters of the prediction horizon. This calls for the need for a policy on moratorium on credit administration to agricultural sector.
Keywords: C01; C13; G20; O40; 330; Agricultural output growth; Asymmetry; Private sector credit; ARDL model; Moratorium